2021
DOI: 10.1029/2020wr027702
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Approach for Improving Prediction of Integrated Hydrologic‐Hydraulic Models by Assessing the Impact of Intrinsic Spatial Scales

Abstract: Riverine modeling is affected by several uncertainties arising from streamflow estimation, quality of topographic data, spatiotemporal scale and resolution, model selection, calibration, and parameterization, among others (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The time steps are adaptively changed according to the criteria in Saksena et al. (2021) in the prescribed range of (0.01–5.121) s. The quantities of interest in each simulation are the flow rate in the stormwater system and the spatial and temporal distributions of the water depth. In Section 4, we analyze uncertainties in these quantities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time steps are adaptively changed according to the criteria in Saksena et al. (2021) in the prescribed range of (0.01–5.121) s. The quantities of interest in each simulation are the flow rate in the stormwater system and the spatial and temporal distributions of the water depth. In Section 4, we analyze uncertainties in these quantities.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the total simulation time of each 1-day rainfall duration event is 3 days and the total simulation time of a 10-day rainfall event is 12 days. The time steps are adaptively changed according to the criteria in Saksena et al (2021) in the prescribed range of (0.01-5.121) s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that river bathymetry impacts the surface-subsurface hydrodynamics at the reach scale. Hydrologic and hydrodynamic processes aggregate and interact differently as we move from single reach to large river networks spanning an entire watershed (Saksena et al, 2021). Therefore, there is a need to evaluate the influence of river bathymetry on hydrologic processes across large river networks.…”
mentioning
confidence: 99%
“…in Saksena et al (2021) for effectively capturing SW-GW interactions in tightly coupled models by considering the intrinsic scales of the surface and subsurface processes in the model structure. It should be noted that the surface and subsurface parameters are uncalibrated and are identical across different bathymetric configurations to avoid biasing the parameters toward any particular configuration.…”
mentioning
confidence: 99%